Analysis of the Arrangement Mechanism of RKA-SKPD in Sampang Regency Focus on SKPD in Jrengik District - Faisol, Faisol; Akbar, Muhammad; Maghfiroh, Nadiya Alfiatur; Watii, Sulaiha; Iswahyudi, Anggi Pradhita (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2023)
The study aims to analyze the mechanism for compiling the RKA-SKPD in Sampang Regency, focusing on the SKPD in Jrengik District. This research method uses descriptive qualitative with data collection through observation, interviews, and documentation. The results of this study indicate that the mechanism for preparing the RKA-SKPD starts from several stages, such as starting from the Musrenbancam to be included in the Renja-SKPD. Next is the preparation of the RKPD (Local Government Work Plan) which refers to the Renja-SKPD, the preparation of the KUA-PPAS (General Budget Policy and Temporary Budget Ceiling Priorities), the preparation of the RKA-SKPD (Work Plan and Budget of the Regional Government Work Unit), the preparation of the APBD Plan and discussion of the RAPBD, finally the ratification and determination of the Sampang Regency APBD (Regional Revenue and Expenditure Budget).